(untitled) (Portuguese Journal of Family Medicine and General Practice, 2010)
Objectives: To explore the opinions and experiences of a range of stakeholders on inter-professional working relationships between community pharmacists and physicians. Study design: Five qualitative studies. Setting: Primary care. Population and Methods: Thirty-one community pharmacists, eight medical and pharmacy leaders, 12 physicians and 21 patients took part in interviews and focus groups reflecting on medicines management services in Portuguese community pharmacy. Data pertaining to inter-professional work was subjected to thematic content analysis with the aid of NVIVO® software. Results: Generally, datasets offer evidence of immature inter-professional working relationships. Data analysis suggests a mismatch between the role pharmacists perceived for themselves and physicians perceptions. A second key theme in explaining barriers to inter-professional work is its perceived benefits. Once again, a mismatch was found between physicians, who gene-rally perceived little benefit for patients or for themselves, and pharmacists, who were keen to collaborate and anticipated be-nefits for patients. A third key theme was that of role encroachment. Analysis suggests that territorial behaviour was evident in both professions. More clinical roles were perceived as an invasion of physicians professional practice both by physicians and community pharmacists, but the latter showed unwillingness to compromise on these newly extended roles. Facilitators mentioned by participants included increasing awareness of the pharmacists role and services, adopting aspects such as joint training, and informal and formal inter-professional meetings. The use of protocols for collaboration and clinical data sharing were also identified as facilitators for inter-professional work. Conclusions: Inter-professional work between community pharmacists and physicians appears to be in an early stage of development. Multi-modal strategies combining top-down and bottom-up approaches seem necessary to advance inter-professional work to a collaboration level that can contribute to patient safety in the medication use process.